2022
DOI: 10.3390/soilsystems6020056
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Uptake by Lettuce Plants and Se Distribution in Soil Chemical Phases Affected by the Application Rate and the Presence of a Seaweed Extract-Based Biostimulant

Abstract: To tackle selenium (Se) malnutrition, biofortification is among the proposed strategies. A biostimulant application in soils is thought to support a plant’s growth and productivity. Biofortification with Se(VI) may lead to a leaching hazard due to the high mobility of Se(VI) in the soil environment. In this study, the effect of the application of two Se(VI) rates—5 and 10 mg kg−1 soil—and a biostimulant on the Se uptake by lettuce plants and on the Se(VI) distribution in soil fractions following the plants’ ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Pekinensis) at a Mo concentration of 0.01-0.1 mg L -1 ( Zhang et al., 2012 ). Se is absorbed by plant roots via the phosphate transporter and thus, induces an antagonistic effect with Mo and P ( Zhang et al., 2012 ; Zafeiriou et al., 2022 ). Landberg and Greger (1994) found that Se depressed the uptake of Cu in pea ( Pisum sativum L. cv.…”
Section: Discussionmentioning
confidence: 99%
“…Pekinensis) at a Mo concentration of 0.01-0.1 mg L -1 ( Zhang et al., 2012 ). Se is absorbed by plant roots via the phosphate transporter and thus, induces an antagonistic effect with Mo and P ( Zhang et al., 2012 ; Zafeiriou et al., 2022 ). Landberg and Greger (1994) found that Se depressed the uptake of Cu in pea ( Pisum sativum L. cv.…”
Section: Discussionmentioning
confidence: 99%
“…Selenium (Se) is a micronutrient generally found in soils in low concentrations, ranging from 0.01 and 2 mg kg −1 , within a global average of 0.4 mg kg −1 [13,14]. The main source of Se intake is through the consumption of vegetable products, whose concentration depends on soil Se levels [15]. Se is an essential micronutrient for humans.…”
Section: Introductionmentioning
confidence: 99%